Postprandial lipemia--effect of lipid-lowering drugs. - Karpe, F (2002)
Exaggerated postprandial hyperlipidemia has been associated with cardiovascular disease. The mechanisms underlying this association are likely to depend on a multitude of effects. Potentially atherogenic remnants of triglyceride-rich lipoproteins (TRL) accumulate in the postprandial state. In addition, TRL may promote the formation of small dense LDL. There are some indications that the postprandial period is a hypercoagulable state and endothelial function seems to be hampered after acute fat intake. Conventional lipid lowering drugs such as statins and fibrates have the potency of reducing postprandial hyperlipidemia, but the fibrates seem to be more effective in this respect. There is a complete lack of prospective studies linking inefficient postprandial lipid metabolism with clinical endpoints and there is also a need to include investigations of postprandial lipid metabolism in the evaluation of novel drugs affecting lipid metabolism and insulin resistance.